2019
DOI: 10.1177/1524839919862796
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Student Health and Academic Data: A County-Level Demonstration Project

Abstract: Students with chronic health conditions miss more school days than their peers and are at increased risk for performing worse on standardized tests and not completing a high school degree. University-based researchers, state government leaders, and a local county school system collaborated to use existing health and academic data to (1) evaluate the strength of the relationship between health status and school performance (absenteeism, grades) and (2) describe the health status of students who are chronically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For example, being a bully victim at age 16-19 is strongly associated with mental health, sleep problems and lower academic performance [7]. In addition, having chronic health conditions like asthma, mental health diagnosis, and attention disorders during kindergarten to secondary is negatively associated with attendance and grade point average [8]. Appropriated sleep is essential for ensuring a good health since differences in sleep timing like bed time, rise time, mid-point of sleep and sleep duration in school-age children and youths show associations with low academic performance, depressive symptoms, high risk of substance use, overweight/obesity, behavioral problems and suicidality [9,10].…”
Section: Health Impact On Performancementioning
confidence: 99%
“…For example, being a bully victim at age 16-19 is strongly associated with mental health, sleep problems and lower academic performance [7]. In addition, having chronic health conditions like asthma, mental health diagnosis, and attention disorders during kindergarten to secondary is negatively associated with attendance and grade point average [8]. Appropriated sleep is essential for ensuring a good health since differences in sleep timing like bed time, rise time, mid-point of sleep and sleep duration in school-age children and youths show associations with low academic performance, depressive symptoms, high risk of substance use, overweight/obesity, behavioral problems and suicidality [9,10].…”
Section: Health Impact On Performancementioning
confidence: 99%
“…Psoriasis in adolescence has been associated with cognitive impairment, the development of addictions (tobacco, alcohol, and drug abuse), and psychiatric symptoms such as attention deficit disorder or attention deficit hyperactivity disorder. [36][37][38][39] These data led to the hypothesis that early psoriasis onset affects the educational development of young patients. In a recent study, our group found that there were no significant associations between early onset of psoriasis and educational level, working activity or living conditions, or with alcohol consumption in adulthood (personal data, submitted for publication).…”
Section: Social Life and Psoriasis School And Universitymentioning
confidence: 99%
“…However, children with chronic illnesses like asthma, migraine headaches, mental health conditions, and eczema/psoriasis/skin disorders have frequent absences due to medical appointments, therapies, or acute episodes of illness. Recurrent absenteeism due to these illnesses hinders academic progress, increases dropout rates and affects professional career success in adulthood (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%